Creative, Critical, and Balanced Thinking Styles among Vocational Education (General Machining) Students - Mohd Sobry, Nur Sabarina; Othman, Hasyamuddin (Research and Innovation in Technical and Vocational Education and Training, 2024)
Creative and critical thinking styles are pivotal for TVET students as they enhance problem-solving capabilities, innovation, creativity, and collaboration, all of which are imperative for success in the contemporary and future sustainable economy. This study aims to identify the creative, critical, and balanced thinking styles among Bachelor of Vocational Education (General Machining) students using the Yanpiaw Creative-Critical Styles questionnaire. The study employs a descriptive design with a quantitative approach. A total of 137 students from the Bachelor of Vocational Education (General Machining) program at the Faculty of Technical and Vocational Education (FPTV), University Tun Hussein Onn Malaysia (UTHM), were selected through a centralized method. The findings reveal that 35 % of students exhibit a critical thinking style, 35% possess a balanced thinking style, 24 demonstrate a creative thinking style, and 6% exhibit an excellent creative thinking style. This study provides a comprehensive overview of the thinking styles among TVET students and underscores the necessity of integrating critical and creative thinking skills into the curriculum to adequately prepare students for future challenges.